FDG PET/CT Can Assess the Response of Locally Advanced Rectal Cancer to Neoadjuvant Chemoradiotherapy: Evidence From Meta-analysis and Systematic Review. (May 2016) - Rymer, Ben; Curtis, Nathan J.; Siddiqui, Muhammed R.S.; Chand, Manish
Abstract : Introduction: Neoadjuvant chemoradiotherapy (CRT) is indicated in locally advanced rectal adenocarcinoma where there is a high risk of local recurrence based on preoperative imaging. Optimal radiological assessment of CRT response is unknown, and metabolic assessment of the tumor has been suggested to gauge response before surgical resection. Patients and Methods: A systematic search of the MEDLINE database was performed using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement to identify papers comparing pre- and post-CRT PET/CT in patients with locally advanced rectal adenocarcinoma with histopathological assessment of tumor regression. Papers were assessed with the QUADAS (Quality Assessment of Diagnostic Accuracy Studies) tool. Meta-analysis was performed for response index (RI) and SUVmax post-CRT. Results: Ten of 69 studies met inclusion criteria containing a total of 538 patients. Methodological quality was high with low heterogeneity. In all studies, post-CRT PET/CT showed a reduction in SUVmax and the RI irrespective of histological findings. Tumors confirmed to have regressed after CRT had a mean difference of 12.21% higher RI (95% confidence interval, 6.51–17.91; P < 0.00001) compared with nonresponders. Mean difference between pre- and post-CRT SUVmax groups was −2.48 (95% confidence interval, −3.06 to −1.89; P < 0.00001) with histopathological responders having a lower post-CRT SUVmax . Conclusions: The available evidence suggests that PET/CT may be a useful addition to the current imaging modalities in the assessment of treatment response.